نمذجة ومحاكاة الألواح الشمسيّة وتحسين استطاعتها باستخدام خوارزمية الاضطراب والمراقبة لملاحقة نقطة الاستطاعة العظمى - ميساء الكنا (Tishreen University, 2016)
يتناول البحث تحليل ودراسة أداء الألواح الشمسية، حيث اخترنا العمل على اللوح (الموديول) الشمسي MSX-50، بالإضافة إلى تحسين استطاعته عن طريق تعقّب نقطة الاستطاعة العظمى MAXIMUM POWER POINT، ويتم ذلك باستخدام مقّطع رافع للجهد الحصول على أكبر استطاعة ممكنة من اللوح الشمسي. تم ّوضع نموذج رياضي مكافئ لعمل اللوح الشمسي الحقيقي (غير مثالي) من خلال دراسة الخلايا الكهروضوئيّة (PHOTOVOLTAIC CELLS)، حيث تمّ استخدام الطريقة التكرارية بالإضافة لخوارزمية نيوتن-رافسون من أجل تحديد قيمة المقاومة التسلسلية للموديول Rs، والمقاومة التفرعية Rp. كما تم تنفيذ خوارزمية الاضطراب والمراقبة Perturbation and Observation P&O، بالإضافة إلى دراسة وتصميم دارة المقطّع chopper واختيار مكونّاتهاL,C (المكثف والملف) بناءً على تحديد كلٍّ من تردد عمل المقطع وعاملي التموج للجهد والتيّار. بناءً على ماسبق، قمنا بإجراء عملية النمذجة للموديول الشمسيMSX-50 باستخدام برنامج MATLAB/SIMULINK،حيث صممنا واجهة مستخدم رسومية GUIلعرض خصائص الموديول وحساب المقاومتينRs,Rp، بالإضافة إلى بناء خوارزمية P&Oوتصميم دارة المقطّع الرافع للجهد(boost-step up). تمّ تطبيق النموذج المقترح على حمولة أومية وفق مبدأ ملاحقة نقطة الاستطاعة العظمىMPP ،ومناقشة النتائج لحالتي توصيل الموديول الشمسي على الحمل مباشرةً،والتوصيل عن طريق مقطّع مقاد بخوارزمية P&O. This paper deals with the analysis and study of performance of solar panels, so we choose working on the solar panel (module) MSX-50, in addition to improve his power by tracking the maximum power point, this is done by using boost (step up) chopper to obtain the largest possible capacity of solar panel. We will determine a mathematical model equivalent to the real solar panel (not ideal) through studying photovoltaic cells, where we will use the iterative method in addition to the Newton-Raphson algorithm in order to determine the value serial resistance of module Rs parallel resistance of module Rp. As has been the implementation of perturbation and observation p&o algorithm in addition studying and designing the circuit of step up (boost) chopper, and selection the components (coil L, capacitor C), based on both the operation frequency f, ripple factor of output voltage and output current . Based on the our study, we have performed a modeling process of the solar module MSX-50 using MATLAB/SIMULINK program, where we designed a graphical user interface GUI to display the module characteristics and calculate resistance Rp and Rs, in addition to build an algorithm p&o and design circuit of boost (step up) chopper. The proposed model has been applied to the ohmic load according to the principle of the maximum power point tracking MPPT, and discuss the results of two cases wich are the following the solar module is connected directly to load, connected through chopper driven by p&o algorithm.